THE INTERRELATIONSHIPS OF PARENTING STYLES, ISLAMIC STUDENTS’ PERSONALITY TRAITS, AND THEIR ACADEMIC ACHIEVEMENTS - Warsah, Idi; Morganna, Ruly; Nooraida, Sharifah; Bakar, Tassim Abu; Prasojo, Zaenuddin Hudi (Psikis : Jurnal Psikologi Islami, 2023)
Prior studies seem to indicate a hypothetical concept that parenting styles and personality traits are of critical factors of academic achievements. Accordingly, the present quantitative study sought to find out the interrelationships of parenting styles, Islamic students’ personality traits, and their academic achievements. 101 Islamic students from an Islamic university in Bengkulu, Indonesia, were randomly assigned to be the samples. Their parents, 202 parents, were also involved to provide the data. The data were collected by distributing valid and reliable questionnaires to students and their parents. The results demonstrated that parenting styles had a positive and significant impact on Islamic students’ personality traits. Parenting styles had a positive and significant impact on Islamic students’ academic achievements. Islamic students’ personality traits had a positive and significant impact on their academic achievements. Lastly, both parenting styles and Islamic students’ personality traits had a positive impact on Islamic students’ academic achievements. It is recommended that further studies be undertaken in wider contexts across diverse students’ characteristics for the sake of revealing different data conditions and meanings.